2011
DOI: 10.3109/07420528.2011.613683
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations of Plasma Homocysteine, Total Antioxidant Status, and Biological Markers of Muscle Injury During Repeated Sprint: Effect on Performance and Muscle Fatigue—A Pilot Study

Abstract: The aim of this study was (i) to evaluate whether homocysteine (Hcy), total antioxidant status (TAS), and biological markers of muscle injury would be affected by time of day (TOD) in football players and (ii) to establish a relationship between diurnal variation of these biomarkers and the daytime rhythm of power and muscle fatigue during repeated sprint ability (RSA) exercise. In counterbalanced order, 12 football (soccer) players performed an RSA test (5 x[6 s of maximal cycling sprint + 24 s of rest]) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
64
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 48 publications
18
64
2
1
Order By: Relevance
“…However, markers of muscle damage increased after the training sessions at 08:00 and 18:00 with a higher rate of increase in the morning for CK (59.9 ± 7.71% versus 29.89 ± 3.08%). These findings are partially in line with the previous studies of Yalcin et al (45) and Hammouda et al (16,17) who showed a significant …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…However, markers of muscle damage increased after the training sessions at 08:00 and 18:00 with a higher rate of increase in the morning for CK (59.9 ± 7.71% versus 29.89 ± 3.08%). These findings are partially in line with the previous studies of Yalcin et al (45) and Hammouda et al (16,17) who showed a significant …”
Section: Discussionsupporting
confidence: 83%
“…This confirms the results of the previous studies in which the authors found that the resting levels of WBC and biochemical markers of muscle damage were higher in the evening close to the acrophase of oral temperature (16)(17)(18)39). These results confirmed the suggestion that circadian changes in core temperature would increase the activity of enzymes, such as phosphofructokinase and LDH (12).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations